2021
DOI: 10.1007/s41348-021-00480-9
|View full text |Cite
|
Sign up to set email alerts
|

Eiphosoma laphygmae, a classical solution for the biocontrol of the fall armyworm, Spodoptera frugiperda?

Abstract: The fall armyworm, Spodoptera frugiperda, an American Lepidoptera, is invasive in Africa and Asia and currently one of the most damaging cereal pests in the tropics. The ichneumonid parasitoid, Eiphosoma laphygmae, is a potential classical biological control agent. We assessed existing knowledge on biology, identified natural distributions, collated reported parasitism rates from field studies and determined which other parasitoids co-occurred. We discussed the suitability of E. laphygmae for classical biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Pair et al1986b;Molina-Ochoa et al 2004;Wyckhuys & O'Neil, 2006;Murúa et al 2009;Virgen et al 2013;Ordóñez-García et al 2015). However, Allen et al (2021) argue that larval parasitism rates are probably largely underestimated in most studies in the Americas because of likely biases in sampling and calculation of parasitism rates. Furthermore, the extensive use of pesticides and Bt crops probably negatively affects natural parasitism rates, either by direct effect on parasitoids or because many parasitoids forage in a density-dependant manner (Ramirez-Romero et al 2007;Desneux et al 2010;Han et al 2016).…”
Section: Action Threshold Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pair et al1986b;Molina-Ochoa et al 2004;Wyckhuys & O'Neil, 2006;Murúa et al 2009;Virgen et al 2013;Ordóñez-García et al 2015). However, Allen et al (2021) argue that larval parasitism rates are probably largely underestimated in most studies in the Americas because of likely biases in sampling and calculation of parasitism rates. Furthermore, the extensive use of pesticides and Bt crops probably negatively affects natural parasitism rates, either by direct effect on parasitoids or because many parasitoids forage in a density-dependant manner (Ramirez-Romero et al 2007;Desneux et al 2010;Han et al 2016).…”
Section: Action Threshold Levelsmentioning
confidence: 99%
“…The recent worldwide invasion of FAW in Africa and Asia has generated interest for CBC using natural enemies from the Americas (Allen et al 2021;Tepa-Yotto et al 2021). However, nowadays, selecting a CBC agent for introduction into a new area is a long process involving careful assessments of potential non-target effects (Hayek et al 2016).…”
Section: Classical Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In Florida, Meagher et al (2016) studied parasitism of S. frugiperda in sweet corn and found that larval parasitism rates were much higher in unsprayed fields (average 44%, up to 91% in some fields) than in fields sprayed with insecticides (15%). The low rates of parasitism mentioned in the literature may also result from underestimations due to sampling and calculation methods ( Vickery 1929 , Allen et al 2021 ). Most studies on field parasitism of S. frugiperda do not separate between larval instars.…”
Section: Prospects For the Cbc Of S Frugiperdamentioning
confidence: 99%
“…Classical biological control, i.e., the introduction of parasitoids from the native range of the pest, is considered in several invaded regions ( Allen et al 2021 ). Should Europe be seriously invaded by S. frugiperda in the future, classical biological control could be envisaged, considering first the most cold-tolerant and most specific, thus safe, American parasitoids.…”
Section: Fall Armyworm Managementmentioning
confidence: 99%